Eco-Friendly Synthesized of CuO Nanoparticles Using Anchusa strigosa L. Flowers and Study its Adsorption Activity - Safaa Ali Khit; Eman Talib Kareem; Ihsan Mahdi Shaheed (مجلة بغداد للعلوم)
Environmentally friendly copper oxide nanoparticles (CuO NPs) were prepared with a green synthesis route via Anchusa strigosa L.  Flowers extract. These nanoparticles were further characterized by FTIR, XRD and SEM techniques. Removing of Gongo red from water was applied successfully by using synthesized CuO NPs which used as an adsorbent material. It was validated that the CuO NPs eliminate Congo red by means of adsorption, and the best efficiency of adsorption was gained at pH (3). The maximum adsorption capacity of CuO NPs for Congo red was observed at (35) mg/g. The equilibrium information for adsorption have been outfitted to the Langmuir, Freundlich, Temkin and Halsey adsorption isotherm types. The temperature thermodynamic parameters like ΔG°, ΔH° and ΔS° have been calculated.